The Role Of Home Healthcare In Improving Quality Of Life And Reducing Hospital Readmission Among Patients With Chronic Diseases (The Review of Diabetic Studies, 2024)
Home healthcare interventions for chronic disease management play a central role in reducing 30-day hospital readmissions and improving patient quality of life. Chronic conditions such as heart failure, chronic kidney disease, hypertension, and diabetes often lead to frequent exacerbations and early rehospitalizations. This synthesis examines structured home-based programs incorporating remote monitoring, patient education, caregiver involvement, and multidisciplinary clinical support. Evidence from randomized controlled trials indicates that combining telemonitoring with personalized follow-up and functional assessments reduces readmission rates and enhances health-related quality of life, particularly in mobility, self-care, and emotional well-being domains. Economic evaluations suggest that while initial investments in technology and staffing may be substantial, cost savings result from decreased hospital utilization and optimized resource use, especially when targeting high-risk populations identified by predictive tools. Ethical considerations emphasize informed consent, privacy protection, cultural sensitivity, equitable access, and caregiver support as essential components for successful implementation. Diverse delivery models, from technology-enabled care to hybrid approaches integrating home visits, demonstrate adaptability across varying healthcare infrastructures. Integrated home healthcare strategies that maintain continuity beyond hospital discharge offer promising avenues for improving clinical outcomes, patient experience, and system efficiency in chronic disease management.